European consumer healthiness evaluation of 'Free-from' labelled food products. (September 2018) - Hartmann, Christina; Hieke, Sophie; Taper, Camille; Siegrist, Michael
Highlights: Products with a free-from label were considered healthier than products without such a label. Strongest effects occurred for free of GMOs and free of palm oil labelling. Various psychological and attitudinal factors influenced healthiness perception. Information-seeking and negative affect were significant predictors of healthiness evaluation. Healthiness evaluation, information-seeking, and preference for naturalness predicted intension to pay a price premium. Abstract: This study aimed to find out how "free-from labelling" shapes consumers' perception of food products and whether the absence of an ingredient is considered an indicator of improved nutritional value of the product. An online survey was conducted in four European countries: the United Kingdom, Sweden, Poland, and France (overall N   =  1950). Four "free-from labels" (lactose-free, gluten-free, GMO-free, and palm oil-free) were tested using different product categories that these labels typically appear on. Healthiness perception was evaluated by comparing products with the free-from labels to identical products without the labels. Potential predictors for healthiness evaluation and intention to pay a price premium were assessed, including nutrition knowledge, information-seeking on food packages, preference for food naturalness, general health interest, trust in actors in the food domain, and affect regarding the absent ingredients. Products with a free-from label were considered healthier than products without such a label, with the strongest effects occurring for labels indicating that products were free of GMOs and free of palm oil. Some differences were observed among countries in the evaluation of the product-label combinations. Information-seeking, nutrition knowledge, and affect were significant predictors of healthiness evaluation. Furthermore, healthiness evaluation, information-seeking, nutrition knowledge, and preference for naturalness predicted intention to pay a price premium for products labelled free-from. When shaping consumers' food shopping behaviour using certain food labels, it is important to know how consumers interpret those labels. A false interpretation of labels might lead to unintended changes in consumer behaviour.